Land Law Reform : Achieving Development Policy Objectives - Bruce, John W.; Giovarelli, Renée; Rolfes, Jr., Leonard; Bledsoe, David; Mitchell, Robert (Washington, DC: World Bank, 2012)
This book examines issues at the forefront of the debate on land law reform, pays particular attention to how reform options affect the poor and disadvantaged, and recommends strategies for alleviating poverty more effectively through land law reform. It reviews the role of the World Bank in land law reform, examining issues of process as well as substance. It also identifies key challenges and directions, and stresses the need to design law reforms in ways that suit diverse economic, legal, and institutional environments. This book is a contribution to comparative thinking on reform of the law relating to land. It examines the implications for land law reform in the broadening of development goals beyond growth to include environmental protection, poverty eradication, and achievement of gender equity, and it reviews a broad range of experience in land law reform. After the introductory chapter, chapter 2 examines how land law reform is achieved through World Bank initiatives. It reviews steps the Bank has taken to achieve comprehensive reforms of land law in the context of natural resource management and land reform programs and land administration projects. It also analyzes lessons learned from various land law reform processes. Chapter 3 addresses reform of rules affecting women's access to and rights in land. The topic is one in which broad recommendations are not necessarily easy due to cultural and other norms governing women's rights and freedoms regarding land. Chapter 4 examines how to develop land markets while minimizing adverse effects and enhancing positive impacts on the poor. Chapter 5 discusses the importance of titling and registration of land rights, reviews concepts that are supported by the Bank in many of its land projects, and describes how titling and registration can affect economic growth and the alleviation of poverty. Chapter 7 deals with issues of equity and poverty in the context of conservation and environmental protection of farms and forests. It examines the role of individual property rights, as well as the legal tools that can be used to encourage conservation. The conclusion draws together significant aspects from all the chapters that are needed for effective land law reform.